PENERAPAN KONSEP SISTEM INFORMASI MANAJEMEN PADA ORGANISASI HPMB-RAYA - Kurnia, Rahmat; Heri, Rahmat Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the application of the Management Information System concept in the student organization, the Bantaeng Raya Student Association (HPMB-Raya). Using a descriptive qualitative approach with a phenomenological method, data were collected through observations and interviews with five core administrators. The results of the study indicate that although HPMB-Raya is aware of the importance of using information technology, information management is still carried out manually and has not been digitally integrated. Some of the main obstacles faced include low digital literacy and limited human resources who understand information systems. However, the administrators showed enthusiasm and readiness to learn and started from simple systems such as archiving using Google Drive. HPMB-Raya has great potential to develop a Management Information System gradually to increase efficiency, transparency, and effectiveness in organizational management in line with the progress of the times.